High Radon Areas and lung cancer prevalence: Evidence from Ireland. (February 2018) - Dempsey, Seraphim; Lyons, Seán; Nolan, Anne
Abstract: This paper examined the relationship between radon risk and lung cancer prevalence using a novel dataset combining spatially-coded survey data with a radon risk map. A logit model was employed to test for significant associations between a high risk of indoor radon and lung cancer prevalence using data on 5590 people aged 50+ from The Irish Longitudinal Study on Ageing (TILDA) and radon risk data from Ireland's Environmental Protection Agency (EPA). The use of data at the individual level allowed a wide range of potentially confounding factors (such as smoking) to be included. Results indicate that those who lived in an area in which 10%–20% of households were above the national reference level (200 Bq/m 3 ) were 2.9–3.1 times more likely to report a lung cancer diagnosis relative to those who lived in areas in which less than 1% of households were above the national reference level. Highlights: We examined the relationship between radon risk and lung cancer prevalence in Ireland. Geo-coded data on radon risk linked to the Irish Longitudinal Study on Ageing (TILDA). Individual-level data allowed inclusion of potentially confounding factors. Those in areas with a higher radon risk more likely to report a lung cancer diagnosis.